Development of Smart Box Learning Media Based On Project Based Learning to Improve the Learning Outcomes of IPAS in Third-Grade of Surjo 03 Elementary School - Intan Tamara Azka Zanuba; Desi Wulandari (Universitas Negeri Semarang, 2026)
Smart Box is a learning medium in the form of an interactive box designed to be attractive and enjoyable, containing visual information such as images, text, or symbols. The Smart Box medium can be an effective tool to support the Project Based Learning process, which emphasizes student activity, creativity, and problem-solving skills. This study aims to describe the development design, feasibility, and effectiveness of the Project Based Learning-based Smart Box learning media on the learning outcomes of IPAS in third-grade of Surjo 03 Public Elementary School. The research method used is research and development with the ADDIE method (analysis, design, development, implementation, and evaluation). The research subjects were 18 third-grade students at Surjo 03 Public Elementary School. Product feasibility was obtained based on validation from media experts, while effectiveness was assessed from the results of students' pre-tests and post-tests when using the learning media. The results showed that the Smart Box media based on Project Based Learning obtained very feasible results in terms of design, material suitability, and learning media feasibility. Therefore, the learning media developed in this study is feasible to be used as an effort to improve student learning outcomes in elementary schools. Further research is recommended to develop learning media similar to different materials or grade levels and to conduct research with a larger sample size in order to obtain broader and more in-depth results.